The Effect of Jigsaw Technique on the Students' Laboratory Material Recognition and Usage Skills in General Physics Laboratory-I Course - Aydin, Abdullah; Biyikli, Filiz (Horizon Research Publishing Co., Ltd., 2017)
This research aims to compare the effects of Jigsaw technique from the cooperative learning methods and traditional learning method on laboratory material recognition and usage skills of students in General Physics Lab-I Course. This study was conducted with 63 students who took general physics laboratory-I course in the department of science education at a state university in Turkey during 2012-2013 academic year. The randomly selected class 1-A consisting of 32 students was assigned as the experiment group (jigsaw group) and the class 1-B consisting of 31 students was assigned as the control group for the study. The Material Recognition and Usage Skills Test (MRUST), Laboratory Skills Evaluation Test (LSET) and Jigsaw Opinion Scale (JOS) were applied. The results were analyzed by SPSS and frequencies were calculated and independent sample t-test was performed. When the analyses of the study were evaluated, it was concluded from the comparison of the experiment group, to which jigsaw technique was applied, and the control group, where traditional learning method was used, that the laboratory skills of the experiment group developed more than that of the control group. Moreover, according to the results of the opinion scale only applied to jigsaw group at the end of the study, it was found that the jigsaw technique created a more effective learning environment in laboratory practices.
Keywords: 4. Education; 3. Good health